Latent friends mining on social networks : a new friends recommendation system for Facebook - Zhang, Dong (2014)
Latent friends of a person mean the persons who have the potential to become friends with the target person. Finding latent friends of a user on Online Social Networks (OSN) and recommending to the user is important for growing a user’s network. Users posts things happening to them on OSN to keep their friends updated. It has been studied that the contents posted by Facebook users are expected to reflect their interests. Thus Facebook statuses can be used to identify one’s interests.